Concurrent Gastric and Colon Adenocarcinoma, a Rare Clinical Presentation - Hengameh Mojdeganlou; Ata Abbasi; Saeid Razavi Dizaji; Mohammad hosseiniazar; rahim asghari (Journal of Research in Applied and Basic Medical Sciences, 2023)
Synchronous (simultaneous) malignant lesions in different organs of a patient are very rare finding. Gastric and colon adenocarcinomas are the most common cancers worldwide but their synchronous occurrence is rare and only four percent of gastric cancer patients have simultaneous colon adenocarcinoma. Here, we report a 64-year-old woman with simultaneous gastric and colon adenocarcinoma presented by abdominal pain and hematemesis.